Common Trends and Shocks to Top Incomes: A Structural Breaks Approach - Jesper Roine; Daniel Waldenström (Research Institute of Industrial Economics (IFN), 2009)
In this paper we use newly compiled top income share data to estimate common breaks and trends across countries over the twentieth century. By using the most re-cent structural breaks techniques, our approach both confirms previous notions and offers new insights. In particular, the division into an Anglo-Saxon and a Continental European experience does not seem to be as clear cut as previously suggested. Some continental European countries have had increases in top income shares, just as in the Anglo-Saxon countries, but typically with a lag. Most notably, we find that the Nordic countries display a marked Anglo-Saxon pattern, with sharply increased top income shares. Unlike in the Anglo-Saxon countries, however, including realized capital gains seems important in these countries. Our results help inform theories about the causes of the recent rise in inequality.
Keywords: C32; D30; N30; 330; Top Incomes; Income Inequality; Economic Development; Common Structural Breaks; Einkommen; Einkommensverteilung; Vermögensverteilung; Wertzuwachssteuer; Entwicklung; Strukturbruch; Nordeuropa; Welt